Exploring the impact of verbal encouragement on strength, endurance, and psychophysiological responses: enhancing teaching strategies in sports science education - Romdhani, Amir; Sahli, Faten; Ghouili, Hatem; Trabelsi, Omar; Rebhi, Mahmoud; Ben Aissa, Mohamed; Saidane, Mouna; Guelmami, Noomen; Dergaa, Ismail; Haddad, Monoem; Zghibi, Makram (Frontiers in Sports and Active Living, 2024)
Introduction This study investigates the effects of teacher verbal encouragement (VE) on strength, endurance, and psychophysiological responses, aiming to enhance teaching strategies in sports science education. Methods Forty-eight sports science students, aged 21.3 ± 0.5 years, participated in this study. The sample was randomly divided into two groups, and a counterbalancing procedure was implemented. Participants completed strength and endurance testing sessions under normal conditions in the first week and repeated similar sessions in the second week with teacher VE. Strength was assessed using the 1RM bench press, squat, and deadlift tests, while endurance was evaluated through 8-minute time trials (8MTT: burpees, box jumps, hand-release push-ups, and sit-ups). Perceived exertion and physical activity enjoyment were investigated using self-reporting instruments. Results The key findings showed that participants lifted greater weights in the 1RM bench press (p < 0.01; r = 0.45, medium to large effect), squat (p < 0.001; Hedges' g = 1.36, large effect), and deadlift tests (p < 0.001; r = 0.79, large effect) and completed a greater number of repetitions in the 8MTT (p < 0.001; r = 0.87, large effect) under VE. Perceived exertion was found to be lower under normal conditions (p < 0.05; r = 0.29, small effect), yet physical activity enjoyment significantly increased under VE (p < 0.05; r = 0.81, large effect). Discussion In conclusion, implementing teacher VE in sports science education can contribute to improved strength and endurance training outcomes and student psychophysiological response.